2023
DOI: 10.1021/acs.jpca.2c06472
|View full text |Cite
|
Sign up to set email alerts
|

1,3 Dipolar Cycloaddition of Münchnones: Factors behind the Regioselectivity

Abstract: The 1,3 dipolar cycloaddition reactions of münchnones and alkenes provide an expedite synthetic way to substituted pyrroles, an exceedingly important structural motif in the pharmaceutical and material science fields of research. The factors governing their regioselectivity rationalization are not well understood. Using several approaches, we investigate a set of 14 reactions (featuring two münchnones, 12 different alkenes, and two alkynes). The Natural Bond Theory and the Non-Covalent Interaction Index anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…[19][20][21][22][23][24][25] In the category of higher order descriptors, one can retrieve the dual descriptor proposed by Morell et al, [26][27][28] the global hyperhardness 26 that has been shown recently to be connected with reactivity through the maximum hardness principle, 29 and lastly the linear response function. 30,31 All of them have afforded valuable insight into, for instance, electrophilicity and nucleophilicity, 32 regioselectivity issues 33,34 (in the case of the dual descriptor), or electronic effects such as inductive or mesomeric ones (encoded in the linear response kernel). 30,[35][36][37] Conversely, one example of third order descriptor that was proposed but overlooked is the P descriptor (corresponding to a global hypersoftness) proposed by Parr and Fuentealba 26 in 1991:…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] In the category of higher order descriptors, one can retrieve the dual descriptor proposed by Morell et al, [26][27][28] the global hyperhardness 26 that has been shown recently to be connected with reactivity through the maximum hardness principle, 29 and lastly the linear response function. 30,31 All of them have afforded valuable insight into, for instance, electrophilicity and nucleophilicity, 32 regioselectivity issues 33,34 (in the case of the dual descriptor), or electronic effects such as inductive or mesomeric ones (encoded in the linear response kernel). 30,[35][36][37] Conversely, one example of third order descriptor that was proposed but overlooked is the P descriptor (corresponding to a global hypersoftness) proposed by Parr and Fuentealba 26 in 1991:…”
Section: Introductionmentioning
confidence: 99%